Application and design of air-to-air variable refrigerant flow systems - Wicoff, Paul (Kansas State University, 2010)
This report addresses the operation, use, and design of air-to-air variable refrigerant flow systems, also known as VRF. Relatively new to the United States, these HVAC systems have potential to reduce energy consumption and utility costs in the correct applications. Although useful in many applications, the best building types for VRF are those requiring a large number of zones and with low ventilation air requirements. The report explains design and system selection considerations and accordingly presents two flowcharts to help designers implement this system. To show how the system compares to traditional technologies in terms of efficiency and cost, the report presents results from several studies comparing VRF to other systems. In addition, an energy modeling study is conducted to clarify the effect of climate on the system; this study established air-to-air VRF as having highest energy consumption in dry, southern climates, based on energy use and operating costs. With this report, HVAC designers can learn when air-to-air VRF is an acceptable method for providing heating and cooling in a building.
Keywords: Variable; Refrigerant; Flow; HVAC; Operation; Design; Engineering, General (0537)